Prevalence and Diversity of Avian Influenza Virus Hemagglutinin Sero-Subtypes in Poultry and Wild Birds in Bangladesh - Hassan, Mohammad M. (Vet Sci, 2020)
Highly pathogenic avian influenza H5 viruses have pandemic potential, cause significant economic losses and are of veterinary and public health concerns. This study aimed to investigate the distribution and diversity of hemagglutinin (HA) subtypes of avian influenza virus (AIV) in poultry and wild birds in Bangladesh. We conducted an avian influenza sero-surveillance in wild and domestic birds in wetlands of Chattogram and Sylhet in the winter seasons 2012–2014. We tested serum samples using a competitive enzyme-linked immunosorbent assay (c-ELISA), and randomly selected positive serum samples (170 of 942) were tested using hemagglutination inhibition (HI) to detect antibodies against the 16 different HA sero-subtypes. All AIV sero–subtypes except H7, H11, H14 and H15 were identified in the present study, with H5 and H9 dominating over other subtypes, regardless of the bird species. The diversity of HA sero-subtypes within groups ranged from 3 (in household chickens) to 10 (in migratory birds). The prevalence of the H5 sero-subtype was 76.3% (29/38) in nomadic ducks, 71.4% (5/7) in household chicken, 66.7% (24/36) in resident wild birds, 65.9% (27/41) in migratory birds and 61.7% (29/47) in household ducks. Moreover, the H9 sero-subtype was common in migratory birds (56%; 23/41), followed by 38.3% (18/47) in household ducks, 36.8% (14/38) in nomadic ducks, 30.6% (11/66) in resident wild birds and 28.5% (2/7) in household chickens. H1, H4 and H6 sero-subtypes were the most common sero-subtypes (80%; 8/10, 70%; 7/10 and 70%; 7/10, respectively) in migratory birds in 2012, H9 in resident wild birds (83.3%; 5/6) and H2 in nomadic ducks (73.9%; 17/23) in 2013, and the H5 sero-subtype in all types of birds (50% to 100%) in 2014. The present study demonstrates that a high diversity of HA subtypes circulated in diverse bird species in Bangladesh, and this broad range of AIV hosts may increase the probability of AIVs’ reassortment and may enhance the emergence of novel AIV strains. A continued surveillance for AIV at targeted domestic–wild bird interfaces is recommended to understand the ecology and evolution of AIVs.